(3QSGdI GdOQ GdjJjes - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s
(3ChdgG (B:s
(3GdMeO ai GdChdi hGdBNQI hHYO agPg QSGdI ai GdJLhjO dcd JGdi bQBf eLjO s
(3BNQgG (B:s
(3hYf EYWGA Mce Gdhba HOhf bWY GdUhJ ef GdJScjf hbdH JGA GdJCfjK gGA hGdJfhjf CdakG hfMh Pdc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B737s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdbQGAGJ hGdJLhjOs